cum fac 2,6(5,8+6,25x(9,3-3,1-(9,76-2x2,88
Răspunsuri la întrebare
Răspuns de
1
2,6{5,8+6,25x[9,3-3,1-(9,76-2x2,88)]}=
=2,6{5,8+6,25x[9,3-3,1-(9,76-5,76)]}=
=2,6[5,8+6,25x(9,3-3,1-4)]=
=2,6(5,8+6,25x2,2)=
=2,6(5,8+13,75)=
=2,6×19,55=
=50,83
=2,6{5,8+6,25x[9,3-3,1-(9,76-5,76)]}=
=2,6[5,8+6,25x(9,3-3,1-4)]=
=2,6(5,8+6,25x2,2)=
=2,6(5,8+13,75)=
=2,6×19,55=
=50,83
andreandrei1:
multumesc acum pot sa fac tema
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă